Colorado AgrAbility: Enhancing the Effectiveness of Outreach Efforts Targeting Farmers and Ranchers With Disabilities - Cindy T. Christen; Robert J. Fetsch (Journal of Applied Communications, 2008)
The Colorado AgrAbility Project (CAP) provides farmers and ranchers who have disabilities with the information and assistive technologies needed to remain successful producers. At present, however, CAP services are underutilized, and the rate of use is declining. This study investigates awareness and attitudinal barriers that might constrain farmers and ranchers with disabilities from seeking assistance. It also identifies preferred outlets for distributing agricultural information in the hope that this will improve the efficacy of outreach efforts. Mail survey research involving 798 randomly selected Colorado farmers and ranchers was conducted in the spring of 2006. Findings suggest that lack of awareness constituted the primary obstacle to increased use of CAP services. Farmers and ranchers were more inclined to refer others in need farmers and ranchers as preferred sources for information and expressed interest in the stories of farmers and ranchers with disabilities who had been helped by CAP. Based on Survey findings, strategies for improving the effectiveness of outreach efforts are proposed, including mobilizing opinion leaders in the farming and ranching communities, recruiting past CAP clients as spokespeople, and placing CAP success stories in agricultural publications.
Keywords: Colorado AgrAbility Project (CAP); Outreach Efforts; target; farmers; ranchers; diabilities